Sporochartines A–E, A New Family of Natural Products from the Marine Fungus Hypoxylon monticulosum Isolated from a Sphaerocladina Sponge - Leman-Loubière, Charlotte; Le Goff, Géraldine; Debitus, Cécile; Ouazzani, Jamal (Frontiers in Marine Science, 2017)
Four new sporochartines B–E were isolated from the marine fungus Hypoxylon monticulosum CLL-205, isolated from a sponge belonging to the Sphaerocladina order and collected in Tahiti coast. Sporochartine A (1), the first representative of this family was previously isolated from the same fungus. The structures of sporochartines B–E were elucidated using 1D and 2D NMR, HRMS and IR data. Their configurations were established according to ROE correlations and comparison with the absolute configuration of sporochartine A (1) previously obtained from X-ray analysis. Sporochartines A–D (2–4) may be derived from endo Diels-Alderase type catalysis and sporochartine E (5) from an exo Diels-Alderase catalysis. The spatial conformation of sporochartines drastically influences the results of the cytotoxic bioassay against HCT-116, PC-3, and MCF-7 human cancer cell lines.